Ocular motor manifestations of neurodegenerative diseases: case reports (Ukrainian Journal of Ophthalmology, 2025)
Background: Ocular motor manifestations (nystagmus and diplopia) do not lead to blindness. However, loss of cognitive abilities in the presence of these manifestations can lead to irreparable social consequences. Therefore, improved diagnostic assessment of ocular motor abnormalities will enable early detection of neurodegenerative diseases, whereas the correction of these abnormalities will prevent the undesirable consequences.Purpose:  To analyze the nature of ocular motor manifestations of neurodegenerative disorders.Material and Methods: Two cases are presented: a case of a partial Parinaud's syndrome, and a case of viral encephalomyelitis. Results: In a case of a partial Parinaud's syndrome, an examination found ocular motor manifestations in the form of incongruous diplopia, nystagmus at near and pupillary light-near dissociation. This allowed suspecting pons lesions, which was confirmed by MRI evidence of multiple small degenerations at the dorsal-medial pons, the location specific for a Parinaud's syndrome. In case 2, the patient was diagnosed with viral encephalomyelitis and substantial bilateral vertical rotational nystagmus, more pronounced in abduction, indicating damage to the brainstem.Conclusion: The pattern and nature of ocular motor abnormalities are helpful in localizing lesions of such deep brain structures as the brainstem and pons. A more thorough study will be beneficial for early diagnostic assessment and timely treatment of neurodegenerative lesions, and, consequently, for preventing undesirable social consequences.
Keywords: ocular motor manifestations; nystagmus; neurodegenerative diseases; diplopia